2005 PRIMARY SCHOOL PARENTS 'VIEWS ON PROGRAM - Mehmet Kaan DEMİR (Fırat University, 2019)
The objective of the research is to shed light on the parent side of the present curriculum and to display the parent views about the elementary curriculum applications. In this context , the principal of the research is evaluating the view of the parents who has fifth grade students in primary schools. The problem of the research is to display the opinions of the parents about 2005 Elementary School Curriculum. The universal of the research consists of the parents of the 5th grades students in Bursa city, Nilüfer and Yıldırım, the towns of Bursa. The research’s sample is comprised of 235 parents of fifth graders that are chosen randomly in this universe. Among the parents 48 of them send their children to private schools and the rest 187 parents send theirs to state schools. According to the results of research, there hasn’t been a meaningful difference between the views of parents about 2005 Elementary School Curriculums and gender, marital status, education level, proximity to child and the place variables of the parents. Although, there has been a meaningful difference between the views of parents about 2005 Elementary School Curriculums and the economic status of parents.